A municipality-based vocational rehabilitation programme for occupationally marginalized citizens: a study protocol for a mixed methods study - Lotte Nygaard Andersen; Mette Jensen Stochkendahl; Kirsten Kaya Roessler (BMC, 2018)
Abstract Background In 2013 vocational rehabilitation programmes (VRP) were given official and legal approval under Danish law to assist occupationally marginalized citizens in gaining general life skills, building their work ability, and increasing their chances of entering the work force. The project's aim is to develop a detailed understanding of the health, psychosocial and work circumstances of participating citizens, and of the important processes and mechanisms underlying the potential effects of participating in the VRP. Methods This study uses an exploratory mixed methods approach with sequential use of quantitative and qualitative methods. Participants are citizens assigned to an individually tailored VRP in the municipality of Sonderborg, Denmark. The quantitative part of the study consists of a longitudinal survey in which participants complete questionnaires at baseline and at follow-up one year later. Variables include demographic and personal characteristics, the latter ascertained through validated questionnaires on well-being, physical activity, interpersonal problems, general health, work ability, kinesiophobia, self-efficacy, depression and anxiety. The qualitative part of the study consists of semi-structured interviews and observations that explore experiences related to VRP. Participants will be recruited and data collected from questionnaires, interviews and observations in the period February 2016 - March 2018. Discussion This research will assemble a unique corpus of knowledge about the characteristics, experiences and outcomes of occupationally marginalized citizens participating in a VRP. It will identify potential enablers and barriers to a successful outcome, and ultimately this knowledge will help inform the future design of individually tailored VRP's. Trial registration ClinicalTrials.gov Identifier: NCT02641704, date of registration December 29, 2015.